Notary Responsibility for Violations & Prohibitions in Connecting Its Position in Related with Notary Code of Conduct - Medira Anggraini (Sultan Agung Notary Law Review, 2021)
For Notaries who do not carry out their obligations as determined by the laws and regulations, the Notary concerned must face the Assembly. Notary Supervisor. In general, the Notary Supervisory Council has the scope of authority to hold sessions to examine any suspected violations of the Notary's Code of Ethics or violations of the implementation of office. Purpose of research it's to Know Responsibilities of Notaries against Violation of the Notary Code of Ethics. The method used in this research is sociological juridical method, the specification in this research is descriptive analytic, the data used are primary data and secondary data, using data collection by interview and literature study, qualitative data analysis, problems analyzed by theory, law enforcement and legal certainty. The results of this study indicate that It is possible for a notary to be included in an illegal act because if there is an element of detrimental to other parties and the loss has a causal relationship between the Notary as the deed maker and the parties entrusting their act to the Notary. Violation of the notary code of ethics can occur due to negligence of responsibility, this is usually the most frequent occurrence. In addition, it could also be due to the absence of strict sanctions and a lot of side with the notary position. The Notary Supervisory Council (MPN) as a body that is trusted to supervise Notaries in their behavior, is considered to have not given any firm action so that the Notary is deterred or afraid of committing violations that have been regulated by existing regulations, this can be an indicator of the occurrence of violations by a Notary.